Pinpointing the vesper bat transposon revolution using the Miniopterus natalensis genome. Issue 1 (December 2016) - Platt, Roy; Mangum, Sarah; Ray, David
Abstract Background Around 40 million years ago DNA transposons began accumulating in an ancestor of bats in the family Vespertilionidae. Since that time, Class II transposons have been continuously reinvading and accumulating in vespertilionid genomes at a rate that is unprecedented in mammals.Miniopterus (Miniopteridae), a genus of long-fingered bats that was recently elevated from Vespertilionidae, is the sister taxon to the vespertilionids and is often used as an outgroup when studying transposable elements in vesper bats. Previous wet-lab techniques failed to identifyHelitrons, TcMariners, or hAT transposons inMiniopterus . Limitations of those methods and ambiguous results regarding the distribution of piggyBac transposons left some questions as to the distribution of Class II elements in this group. The recent release of theMiniopterus natalensis genome allows for transposable element discovery with a higher degree of precision. Results Here we analyze the transposable element content ofM. natalensis to pinpoint with greater accuracy the taxonomic distribution of Class II transposable elements in bats. These efforts demonstrate that, compared to the vespertilionids, Class II TEs are highly mutated and comprise only a small portion of theM. natalensis genome. Despite the limited Class II content, M. natalensis possesses a limited number of lineage-specific, low copy number piggyBacs and shares several TcMariner families with vespertilionid bats. Multiple efforts to identifyHelitrons, one of the major TE components of vesper bat genomes, using de novo repeat identification and structural based searches failed. Conclusions These observations combined with previous results inform our understanding of the events leading to the unique Class II element acquisition that characterizes vespertilionids. While it appears that a small number of TcMariner and piggyBac elements were deposited in the ancestralMiniopterus  + vespertilionid genome, these elements are not present inM. natalensis genome at high copy number. Instead, this work indicates that the vesper bats alone experienced the expansion of TEs ranging fromHelitrons to piggyBacs to hATs.